Step * 1 2 1 1 2 1 1 of Lemma sequence-class-program_wf


1. Info Type
2. Type
3. Type
4. valueall-type(A)
5. es EO+(Info)@i'
6. E@i
⊢ ∀xpr:hdataflow(Info;A). ∀ypr:hdataflow(Info;B). ∀zpr:hdataflow(Info;A).
    ((∀u:E List. ∀x:E.
        (u [x] ≤ [] [e]
         (¬↑(bag-null(snd(xpr*(map(λx.info(x);u))(info(x))))
           ∧b bbag-null(snd(ypr*(map(λx.info(x);u))(info(x)))))))))
     ((snd(xpr*(map(λx.info(x);[]))(info(e))))
       (snd(mk-hdf(S,a.case S
          of inl(XY) =>
          let X,Y XY 
          in let X',bx X(a) 
             in let Y',by Y(a) 
                in if bag-null(bx) ∧b bbag-null(by)) then let Z',bz zpr(a) in <inr Z' bz> else <inl <X', Y'>bx> \000Cfi 
          inr(Z) =>
          let Z',b Z(a) 
          in <inr Z' b>;S.case of inl(XY) => ff inr(Z) => hdf-halted(Z);inl <xpr, ypr>)*(map(λx.info(x);[]))(info(\000Ce))))
       ∈ bag(A)))
BY
(AllReduce THEN (UnivCD THENA Auto)) }

1
1. Info Type
2. Type
3. Type
4. valueall-type(A)
5. es EO+(Info)@i'
6. E@i
7. xpr hdataflow(Info;A)@i
8. ypr hdataflow(Info;B)@i
9. zpr hdataflow(Info;A)@i
10. ∀u:E List. ∀x:E.
      (u [x] ≤ [e]
       (¬↑(bag-null(snd(xpr*(map(λx.info(x);u))(info(x)))) ∧b bbag-null(snd(ypr*(map(λx.info(x);u))(info(x))))))))@i
⊢ (snd(xpr(info(e))))
(snd(mk-hdf(S,a.case S
   of inl(XY) =>
   let X,Y XY 
   in let X',bx X(a) 
      in let Y',by Y(a) 
         in if bag-null(bx) ∧b bbag-null(by)) then let Z',bz zpr(a) in <inr Z' bz> else <inl <X', Y'>bx> fi 
   inr(Z) =>
   let Z',b Z(a) 
   in <inr Z' b>;S.case of inl(XY) => ff inr(Z) => hdf-halted(Z);inl <xpr, ypr>)(info(e))))
∈ bag(A)


Latex:


Latex:

1.  Info  :  Type
2.  A  :  Type
3.  B  :  Type
4.  valueall-type(A)
5.  es  :  EO+(Info)@i'
6.  e  :  E@i
\mvdash{}  \mforall{}xpr:hdataflow(Info;A).  \mforall{}ypr:hdataflow(Info;B).  \mforall{}zpr:hdataflow(Info;A).
        ((\mforall{}u:E  List.  \mforall{}x:E.
                (u  @  [x]  \mleq{}  []  @  [e]
                {}\mRightarrow{}  (\mneg{}\muparrow{}(bag-null(snd(xpr*(map(\mlambda{}x.info(x);u))(info(x))))
                      \mwedge{}\msubb{}  (\mneg{}\msubb{}bag-null(snd(ypr*(map(\mlambda{}x.info(x);u))(info(x)))))))))
        {}\mRightarrow{}  ((snd(xpr*(map(\mlambda{}x.info(x);[]))(info(e))))
              =  (snd(mk-hdf(S,a.case  S
                    of  inl(XY)  =>
                    let  X,Y  =  XY 
                    in  let  X',bx  =  X(a) 
                          in  let  Y',by  =  Y(a) 
                                in  if  bag-null(bx)  \mwedge{}\msubb{}  (\mneg{}\msubb{}bag-null(by))
                                      then  let  Z',bz  =  zpr(a) 
                                                in  <inr  Z'  ,  bz>
                                      else  <inl  <X',  Y'>,  bx>
                                      fi 
                    |  inr(Z)  =>
                    let  Z',b  =  Z(a) 
                    in  <inr  Z'  ,  b>S.case  S  of  inl(XY)  =>  ff  |  inr(Z)  =>  hdf-halted(Z);inl  <xpr,  ypr>)*(map(\mlambda{}\000Cx.info(x);[]))(info(e))))))


By


Latex:
(AllReduce  THEN  (UnivCD  THENA  Auto))




Home Index